Cep97 Is Required for Centriole Structural Integrity and Cilia Formation in Drosophila - Dobbelaere, Jeroen; Schmidt Cernohorska, Marketa; Huranova, Martina; Slade, Dea; Dammermann, Alexander (Current biology, 2020)
Centrioles are highly elaborate microtubule-based structures responsible for the formation of centrosomes and cilia. Despite considerable variation across species and tissues within any given tissue, their size is essentially constant [1, 2]. While the diameter of the centriole cylinder is set by the dimensions of the inner scaffolding structure of the cartwheel [3], how centriole length is set so precisely and stably maintained over many cell divisions is not well understood. Cep97 and CP110 are conserved proteins that localize to the distal end of centrioles and have been reported to limit centriole elongation in vertebrates [4, 5]. Here, we examine Cep97 function in Drosophila melanogaster. We show that Cep97 is essential for formation of full-length centrioles in multiple tissues of the fly. We further identify the microtubule deacetylase Sirt2 as a Cep97 interactor. Deletion of Sirt2 likewise affects centriole size. Interestingly, so does deletion of the acetylase Atat1, indicating that loss of stabilizing acetyl marks impairs centriole integrity. Cep97 and CP110 were originally identified as inhibitors of cilia formation in vertebrate cultured cells [6], and loss of CP110 is a widely used marker of basal body maturation. In contrast, in Drosophila, Cep97 appears to be only transiently removed from basal bodies and loss of Cep97 strongly impairs ciliogenesis. Collectively, our results support a model whereby Cep97 functions as part of a protective cap that acts together with the microtubule acetylation machinery to maintain centriole stability, essential for proper function in cilium biogenesis.
Keywords: kultivované buňky; Cells, Cultured; Cilia; centrioles; centrioly; Centrioles; Microtubule-Associated Proteins; Animals; Centrosome; bazální tělíska; cilia; zvířata; Basal Bodies; proteiny asociované s mikrotubuly; morfogeneze; centrozom; cilie; Drosophila melanogaster; organelle biogenesis; Morphogenesis